2023
DOI: 10.3389/fimmu.2023.1120670
|View full text |Cite
|
Sign up to set email alerts
|

Integrated bioinformatic analysis of mitochondrial metabolism-related genes in acute myeloid leukemia

Abstract: BackgroundAcute myeloid leukemia (AML) is a common hematologic malignancy characterized by poor prognoses and high recurrence rates. Mitochondrial metabolism has been increasingly recognized to be crucial in tumor progression and treatment resistance. The purpose of this study was to examined the role of mitochondrial metabolism in the immune regulation and prognosis of AML.MethodsIn this study, mutation status of 31 mitochondrial metabolism-related genes (MMRGs) in AML were analyzed. Based on the expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 102 publications
0
10
0
Order By: Relevance
“…High expression of these genes was associated with the concomitant expression of unfavorable metabolic regulatory genes (see Section 3 ). Another bioinformatical study based on bone marrow gene expression profiles classified patients into favorable and adverse prognostic subsets based on their mitochondrial metabolic gene profile [ 71 ], and this study also suggested that high-risk patients showed a higher infiltration of immunocompetent cells and, especially, M2 macrophages, γδ T cells, MDSCs and Treg cells.…”
Section: Monocytic Fab-m4/m5 Aml Cell Differentiation: Morphological ...mentioning
confidence: 84%
See 3 more Smart Citations
“…High expression of these genes was associated with the concomitant expression of unfavorable metabolic regulatory genes (see Section 3 ). Another bioinformatical study based on bone marrow gene expression profiles classified patients into favorable and adverse prognostic subsets based on their mitochondrial metabolic gene profile [ 71 ], and this study also suggested that high-risk patients showed a higher infiltration of immunocompetent cells and, especially, M2 macrophages, γδ T cells, MDSCs and Treg cells.…”
Section: Monocytic Fab-m4/m5 Aml Cell Differentiation: Morphological ...mentioning
confidence: 84%
“…As outlined above, mitochondria-related reprogramming is important in AML, and two recent studies therefore investigated the possible prognostic impact of mitochondria-related genes for patients receiving conventional intensive antileukemic therapy [ 70 , 71 ]. The first study was based on an analysis of 149 patients, and they constructed a prognostic model based on the expression/RNA levels of the following four metabolic genes (information from the Gene database, accessed on 6 October 2023) [ 70 ]: 4-hydroxyphenylpyruvate dioxygenase like ( HPDL , chromosome 1).…”
Section: Variations In the Mitochondrial Energy Metabolism Of Aml Cel...mentioning
confidence: 99%
See 2 more Smart Citations
“…First, monocytic differentiation reflected by the FAB classification is associated with resistance to venetoclax-based (i.e., a BCL-2 inhibitor), and this resistance seems to be due to decreased functional importance of BCL-2 and thereby altered regulation of apoptosis and mitochondrial energy metabolism in monocytic AML cells, including leukemic stem cells [ 30 , 31 , 50 , 77 ]. Second, differential expression of mitochondria-related genes is important for chemoresistance and seems to have an independent prognostic impact in AML [ 78 ]. Third, a subset of AML patients show mutations in genes that encode proteins in the electron transport complexes (Complex I/III/IV, ATP synthase), and mutations in the mitochondrial NADH dehydrogenase subunit 4 (a component of Complex I) seem to have a prognostic impact in adult AML [ 79 , 80 ].…”
Section: Discussionmentioning
confidence: 99%